POSSIBILITY TO CHANGE THE IDEAS OF CORRUPTION IN THE SOCIETY - V. V. Vasina; R. G. Khalitov; I. M. Yusupov (Russian Journal of Economics and Law)
The authors present a model of psychosocial dissonance as a contradiction of ideas of interaction subjects (personalities, groups, societies) and arising psychological tension, which has two outcomes: development and destruction. Corruption is viewed from the point of view of the psychosocial dissonance model as a factor of changes in the life of the society.